Scary Stories to Tell in the Dark : Scary Stories #1 - Schwartz, Alvin, 1927-1992; Helquist, Brett (New York, N.Y. : Harper, 2010)
Tapped from the oral traditions of American folklore, these ghost stories and tales of weird happenings, witches, and graveyards have startling, funny, or surprising endings.
"AAAAAAAAAAAH!" -- The big toe -- The walk -- "What do you come for?" -- Me tie dough-ty walker -- A man who lived in Leeds -- Old woman all skin and bone -- The thing -- Cold as clay -- The white wolf -- The haunted house -- The guests -- The hearse song -- The girl who stood on a grave -- A new horse -- Alligators -- Room for one more -- The wendigo -- The dead man's brains -- "May I carry your basket?" --The hook -- The white satin evening gown -- High beams -- The babysitter -- The viper -- The attic -- The slithery-dee -- Aaron Kelly's bones -- Wait till Martin comes -- The ghost with the bloody fingers.
Includes bibliographical references (p. 105-111)
Ages 9 up.
Keywords: Ghost stories, American; Tales -- United States; Ghosts -- Folklore; Horror stories; Folklore